Availability and affordability of essential medicines and diagnostic tests for diabetes mellitus in Africa - Kibirige, Davis; Olum, Ronald; Kyazze, Andrew Peter; Bongomin, Felix; Sanya, Richard E. (Tropical Medicine & International Health, 2022)
To investigate the current status of the availability and affordability of specific essential medicines and diagnostics for diabetes in Africa. Methods: Systematic review and meta-analysis. Studies conducted in Africa that reported any information on the availability and affordability of short-acting, intermediate-acting, and premixed insulin, glibenclamide, metformin, blood glucose, glycated haemoglobin or HbA1c, and lipid profile tests were included. Random-effect model metaanalysis and descriptive statistics were performed to determine the pooled availability and affordability, respectively. Results: A total of 21 studies were included. The pooled availability of each drug was as follows: short-acting insulin 33.5% (95% CI: 17.8% - 49.2%, I2=95.02%), intermediate-acting insulin 23.1% (95% CI: 6.3% - 39.9%, I2=91.6%), premixed insulin 49.4% (95% CI: 24.9% - 73.9%, I2=90.57%), glibenclamide 55.9% (95% CI: 43.8% - 68.0%, I2=96.7%), and metformin 47.0% (95% CI: 34.6% - 59.4, I2=97.54%). Regarding diagnostic tests, for glucometers the pooled availability was 49.5% (95% CI: 37.9% - 61.1%, I2=97.43%), for HbA1c 24.6% (95% CI: 3.1% - 46.1%, I2=91.64), and for lipid profile tests 35.7% (95% CI: 19.4% - 51.9%, I2=83.77%). The median (IQR) affordability in days’ wages was 7 (4.7- 7.5) for short-acting insulin, 4.4 (3.9-4.9) for intermediate-acting insulin, 7.1 (5.8-16.7) for premixed insulin, 0.7 (0.7- 0.7) for glibenclamide, and 2.1 (1.8-2.8) for metformin. Conclusion: The availability of the five essential medicines and three diagnostic tests for diabetes in Africa is suboptimal. The relatively high cost of insulin, HbA1c, and lipid profile tests is a significant barrier to optimal diabetes care. Pragmatic country-specific strategies are urgently needed to address these inequities in access and cost.
Keywords: Availability; Affordability; Essential medicines; Diagnostic tests; Diabetes mellitus